Antibiofilm properties, cytotoxicity, and effect on protease activity of antibiotics and EGCG-based medications for endodontic purposes - Chrisostomo, Daniela Alvim [UNESP]; Pereira, Jesse Augusto [UNESP]; Scaffa, Polliana Mendes Candia; Gouveia, Zach; Abuna, Gabriel Flores; Plotnikov, Sergey V.; Prakki, Anuradha; Duque, Cristiane [UNESP] (Elsevier, 2025)
Objective: To evaluate the effect of two intracanal medications (IM) containing epigallocatechin-3-gallate (EGCG) with fosfomycin (FOSFO) and a triantibiotic combination of metronidazole, ciprofloxacin and fosfomycin (TRI), compared to controls calcium hydroxide (CH), all dissolved in polyethylene glycol 400 (PEG) on multispecies biofilms, fibroblast toxicity and on collagenolytic and gelatinolytic activities detected in radicular dentin. Methods: The antibiofilm effect and cytotoxicity of medications containing EGCG + FOSFO, TRI or CH were evaluated on multispecies biofilms formed in bovine root dentin specimens by confocal microscopy and on fibroblasts by resazurin assays, respectively. The inhibition of protease activity of each IM was evaluated by measuring collagenolytic enzyme activity by ELISA (Enzyme-linked immunosorbent assay) and gelatinolytic activity by metalloproteinases (MMPs) using in situ zymography in radicular dentin specimens. Results: PEG containing EGCG+FOSFO, PEG+TRI, and PEG+CH significantly reduced multispecies biofilms in radicular dentin tubules. At the concentrations tested, those IM were not toxic to fibroblasts. Additionally, all IM presented anti-collagenolytic activity by reducing telopeptide fragments released from radicular dentin compared to PEG carrier and water controls. In situ gelatinolytic activity, assessed via fluorescence levels, was significantly lower in radicular dentin adjacent to PEG containing CH, EGCG+FOSFO, or TRI compared to PEG and water controls. Conclusion: EGCG+FOSFO and TRI in PEG-400 exhibited antibiofilm, anti-collagenolytic and anti-gelatinolytic properties at concentrations that were non-toxic to fibroblasts, making them feasible intracanal medications for endodontic applications. Clinical significance: EGCG-based medications enhance the efficacy of endodontic treatment by providing antibiofilm, anti-collagenolytic, and anti-gelatinolytic properties, contributing to the preservation of root structure and improved treatment outcomes.
Keywords: Antibiotics; Antimicrobial; Biofilms; Collagen degradation; Endodontics; Metalloproteinases